Solubility and diffusion of chemical elements in high-temperature superconductors - Alfeev, V. N.; Bakuntseva, M. V.; Gorbik, P. P.; Zaitov, F. A.; Shalyapina, G. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2001)
Solubility and diffusion of admixtures of cationic (Ni, In, Sn, Au, Cd, Bi, Ag, Y, Hg) and anionic (S, Se) subsystems in structural-inhomogeneous HTSC-polycrystalline YBa2Cu307-δ and (PbxBi1-x)2Ca2Sr2Cu3Oy were studied. Methods of radioactive indicators, X-ray spectral microanalysis, scanning electron microscopy, and electron Auger spectroscopy were used.